Effect of Alkaline Treatment on The Mechanical Properties of Pineapple Leaf Fiber Composite Material - M Febriyan Baruna Putra; Delima Yanti Sari; Hendri Nurdin; Rodesri Mulyadi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
Utilization of natural fiber waste, especially pineapple dau fiber, is a major concern and continues to be developed to utilize and optimize plantation waste as a material that is more environmentally friendly, energy efficient and inexpensive. The purpose of this study was to determine the effect of alkaline treatment on the mechanical properties of pineapple leaf fiber composite material as an appropriate alternative material. The method in this research is the experimental method, where the research was carried out by giving variations in the percentage of alkaline 10% and 20%. The results of the research on the composite material of pineapple leaf fiber using tensile testing showed that giving alkaline treatment with a percentage of 20% made the fiber stronger but brittle. In addition, the orientation direction and immersion time also affect the tensile strength of the fibers. Pemanfaatan limbah serat alam khususnya serat dau nanas menjadi bahan alternatif menjadi perhatian utama serta terus dikembangkan guna memanfaatkan dan mengoptimalkan limbah perkebunan sebagai bahan material yang lebih ramah lingkungan, hemat energi, dan murah. Tujuan penelitian ini untuk mengetahui pengaruh perlakuan alkali terhadap sifat mekanik material komposit serat daun nanas sebagai bahan alternatif tepat guna. Metode dalam penelitian ini yaitu metode eksperimen, dimana penelitian dilakukan dengan pemberian variasi persentase alkali 10% dan 20%. Hasil penelitian material komposit serat daun nanas dengan menggunakan pengujian tarik menunjukkan bahwa pemberian perlakuan alkali dengan persentase 20% membuat serat menjadi lebih kuat namun bersifat getas. Selain itu, arah orientasi dan waktu perendaman juga mempengaruhi kekuatan tarik serat.